Design Aspects of a Broadband Beam-Reconfigurable Leaky-Wave Antenna - Abdo-Sánchez, María Elena; Palacios, David; Frías, C.; Ng-Molina, Francisco Yak; Martín-Guerrero, Teresa María; Camacho-Peñalosa, Carlos (IEEE Antennas and Propagation Society, 2016)
Design aspects of a novel beam-reconﬁgurable pla-nar series-fed array are addressed to achieve beam steering with frequency tunability over a relatively broad bandwidth. The design is possible thanks to the use of the complementary strip-slot, which is an innovative broadly matched microstrip radiator, and the careful selection of the phase shifter parameters.
Keywords: Antenas; Antenna; Beam-reconfigurable antenna; Broadband antenna